Design and creation of a educational computer material (YAKU 1.0) relating to the theme of the water and integrated management (Revista de Investigaciones Universidad del Quindío, 2010)
Through this research we were able to create and design an educational computer material (ECM) named YAKU 1.0, in order to promote in the users of different educational communities, opportunities for reflection, analysis and discussion regarding the conservation and efficient use of water. YAKU 1.0 is a multimedia learning material on CD ROM, about the water and water management in an integrated way for life and sustainable development, therefore it was used multimedia (text, images, animations and sound) and development tools like Neobook 5.5 as the main utility, Windows Movie Maker 5.1, Flash MX, photo editors, among others. Also, in this research it was possible to develop a unique and dynamic methodology, attached to the socio-educational and cultural context. We applied the main parameters considered for the creation and design of ECM taking into account two phases: Phase 1: Pre-design and learning conditions of the ECM, Phase 2: Processing and technical conditions of the ECM. All the above, in order to generate a field of action allowing the formation of ECM development groups in different areas of knowledge, likewise the research aims to promote the use of computers and TIC as an important learning tool in the interaction of knowledge in the water topic.
Keywords: educational computer material; YAKU; classroom; material didactic; tool; multimedia; water integral management